Intertemporal choice of marine ecosystem exploitation - Lars J. Ravn-Jonsen (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2009)
The term 'Fishing Down Marine FoodWebs' describes the gradual transition in landing from marine ecosystems towards organisms lower in the food web. To address this issue and the need to manage the marine ecosystem in a broader perspective, Ecosystem Management is recommended. Ecosystem Management, however, requires models that can link the ecosystem level to the operation level, so this paper examines an ecosystem production model and shows that it is suitable for applying ground rent theory. This model is the simplest possible that incorporates the principles of size as the main determinant of the predator-prey interaction, the inclusion of mass balance in the predator-prey allocation, and mortality and somatic growth as consequences of the predator-prey allocation. The model needs to be parameterized for the specific ecosystem and the price and cost functions must be established empirically before drawing the conclusion that Fishing Down Marine Food Webs is economically detrimental can be established directly. Nevertheless, the model does reveal a need for intertemporal balance with respect to both fish size and harvest volume. These aspects are not addressed in any systematic way at the ecosystem level in the present management. Therefore, economic predictions for an ecosystem managed as a common pool resource must be that the exploitation probably are conducted at lower sized than optimum. In addition, given its population stock approach, the present management probably overlooks the ability of an ecosystem to sustain total volume of harvest. Given the two aspects of intertemporal choice revealed by the model, the conclusion must be that the Fishing Down Marine Food Webs is probably driven by the current management's inability to conduct adequate intertemporal balancing; therefore, it is probably detrimental from an economic point of view. The marine ecosystem therefore requires an ecosystem management for economic reasons; in this context, models like the one presented here can serve as useful planning tools.
Keywords: 330; Umweltökonomik; Meeresnutzung; Fischerei; Theorie